2019
DOI: 10.1016/j.bja.2019.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive cardiac output monitoring in a porcine model using the inspired sinewave technique: a proof-of-concept study

Abstract: Background Cardiac output monitoring can support the management of high-risk surgical patients, but the pulmonary artery catheterisation required by the current ‘gold standard’—bolus thermodilution —has the potential to cause life-threatening complications. We present a novel noninvasive and fully automated method that uses the inspired sinewave technique to continuously monitor cardiac output . Methods Over successive bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…In another research, a proof-of-concept study in eight different pigs concluded that IST and thermodilution have good agreement in capturing the trend when the cardiac output changed [7]. Our study fitted into the gap of the absolute value comparison.…”
Section: Discussionmentioning
confidence: 57%
“…In another research, a proof-of-concept study in eight different pigs concluded that IST and thermodilution have good agreement in capturing the trend when the cardiac output changed [7]. Our study fitted into the gap of the absolute value comparison.…”
Section: Discussionmentioning
confidence: 57%
“…In this work, we demonstrated the ability of the IST, a relatively simple to implement lung function test, as a diagnostic tool. The IST results are reliable and clinically meaningful 17 , 18 . Previous studies indicated that, in ventilated subjects, the IST could measure the effective lung volume (“baby lung”) and capture the pulmonary blood flow trend 17 , 18 .…”
Section: Discussionmentioning
confidence: 81%
“…The IST results are reliable and clinically meaningful 17 , 18 . Previous studies indicated that, in ventilated subjects, the IST could measure the effective lung volume (“baby lung”) and capture the pulmonary blood flow trend 17 , 18 . The IST does not require special, forced manoeuvres, which patients often find challenging and uncomfortable.…”
Section: Discussionmentioning
confidence: 81%
“…Theory dictates that in the completely homogeneously ventilated and perfused lung, the values of ELV and Qp recovered from the IST are independent of the tracer gas period used. The IST accuracies of ELV and Qp values are published elsewhere A c c e p t e d M a n u s c r i p t [14,15]. However, as the degree of heterogeneity increases, the ELV and Qp values (based on the assumption of perfect homogeneity) begin to diverge from true values, and moreover, those values recovered from periods of 60 and 180s also diverge from each other.…”
Section: Inspired Sinewave Test Heterogeneity Indicesmentioning
confidence: 99%